BASIC GENETIC ENGINEERING TECHNIQUES INVOLVED IN HUMAN CLONING: A NARRATIVE REVIEW - Faiza Putri Yuliastri Uri; Sindi Wulan Safitri; Novriyani Amran; Mubdiah Zainudin; Rayyan Zulfanafilah Lasanudin; Fina Mawaddah (JIMR : Journal Of International Multidisciplinary Research, 2025)
Research this aim for study view ethics and morals towards practice cloning man based on study literature scientific method research used is studies literature with approach qualitative through analysis content to three journal that discusses human cloning from perspective ethics biotechnology , social ethics and morals, as well as ethics religious. Data analyzed with grouping ideas and arguments main to in themes relevant ethics. Study results show that human cloning is seen potential threaten dignity and uniqueness identity human, causing risk biological like abnormalities genetics and disorde rs development, as well as trigger problem social in the form of inequality, objectification humans and change structure social. Besides that, from corner view ethics religious, cloning man considered contra dictory with spiritual values regarding essence creation and holiness life human beings. The conclusion of study This confirm that although engineering genetics own potential significant scientific and therapeu tic benefits, the application of human cloning must be restricted in a way strict through principle clear ethics and oversight multidiscipline ry so that development technology still in line with fundamental moral, social and humanitarian values.